Prenatal care using a mixed approach during the COVID-19 pandemic: patients' satisfaction study in a tertiary hospital in Peru - Rommy Helena Novoa; Xin Huang-Yang; Alonso Gayoso-Liviac; Luis Meza-Santibañez; Juan Carlos Bazo-Alvarez; Juan Torres-Osorio; Noe Rodríguez-Hilario; Walter Ventura (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to evaluate patients' satisfaction of mixed prenatal care during the COVID-19 pandemic in a tertiary hospital in Lima, Peru. Methods: we conducted a cross-sectional evaluation of satisfaction in patients receiving mixed prenatal care that includes in-person and virtual visits. All women who gave a written consent between June and July 2021 were included. The survey was based on the Short Assessment of Patient Satisfaction (SAPS) scale which evaluated seven dimensions of satisfaction: access and facilities, effectiveness, information, technical skills, participation, relationship, and general satisfaction. Results: the overall satisfaction on mixed prenatal care was 3.28 ± 0.71. The mean SAPS score was 33.88 (SD = 5.56). In total, 144 patients (65%) preferred the mixed prenatal care. The mean maternal age of 221 included pregnant women was 30 years and the mean gestational age at the first appointment was 24 weeks. Overall, 88.2% of patients had up to 6 visits among virtual and in-person. Patients with non-health insurance had lower rates of satisfaction when compared with pregnant women with national health insurance (p=0.026). Conclusions: women receiving the mixed prenatal care during the COVID-19 pandemic reported a high level of satisfaction. In general, pregnant women would recommend mixed prenatal care.